Bookkeeping for foreign companies: The required level of English language : https://doi.org/10.5937/etp2501115V - Vukčević, Vanja (Ekonomija - teorija i praksa, 2025)
This study examines the importance of maintaining accurate business records in foreign companies operating in the Republic of Serbia, with a focus on employees' proficiency in English as it pertains to accounting. The goal of the work was to highlight the significance of obtaining an English language proficiency certificate for employees involved in bookkeeping for foreign companies in Serbia. The results demonstrate significant differences in the reliability of business reports prepared by professionals with a valid English language certificate compared to those without one. The practical implications of this study emphasize the necessity of certified employees in foreign companies, particularly in accounting, auditing, and the preparation of annual reports.